Remote government. Management of the presidential office with the use of information and communication technologies. Peru Case - Cáceres Arce, Jorge Luis; Del Carpio Ugarte, César Alejandro (REVISTA ELECTRONICA IBEROAMERICANA, 2024)
The objective of this academic contribution is to describe the problems faced by the Government of the Republic of Peru in the face of the need for educational representation of the Peruvian State before international organizations, and also to develop the regulatory content that can be the subject of an Organic Law of the Hand with motivated constitutional development and its constitutional development function. Therefore, the legal formula for reform of the Organic Law of the Executive Branch is valid, which regulates the exercise of the charge of the “presidential office”, and exceptionally its remote management, this interpretation is carried out by adapting the constitutional text to the current and current problem, then appropriate and reasonable solutions.